A path priority-based task scheduling algorithm for heterogeneous distributed systems. (1st January 2014) - Eswari, R.; Nickolas, S.; Arock, Michael
Finding an effective schedule of tasks of distributed applications on the heterogeneous distributed computing systems is a trade-off between minimising the makespan and maximising the processor utilisation. The performance can be exploited in these systems through proper scheduling of application tasks. In this paper, a new task scheduling algorithm, called path-based heuristic task scheduling (PHTS) algorithm is proposed. The performance of the proposed algorithm is experimentally compared with the three existing scheduling algorithms. The results show that the PHTS algorithm outperforms other algorithms in terms of schedule length ratio, speedup and efficiency for applications with more tasks.